Acute interstitial nephritis associated with ingesting a Momordica charantia extract: A case report. Issue 27 (9th July 2021) - Bae, Wooram; Kim, Seongmin; Choi, Jungyoon; Lee, Tae Won; Bae, Eunjin; Jang, Ha Nee; Jung, Sehyun; Lee, Seunghye; Chang, Se-Ho; Park, Dong Jun
Abstract: Rationale: Momordica charantia is often used to treat type 2 diabetes mellitus in Korea. Drug-induced acute interstitial nephritis (AIN) accounts for 60% to 70% of AIN cases. However, only 1 case of AIN associated with ingesting M charantia has been reported in the English literature. We report an extremely rare case of AIN that occurred after a patient ingested a pure M charantia extract over 7 months. Patient concerns: A 60-year-old Korean woman was admitted to our hospital for a renal biopsy. Her renal function had decreased gradually over the last 9 months without symptoms or signs. Diagnosis: Her blood urea nitrogen and serum creatinine levels were 29.7 mg/dL (range: 8.0–20.0 mg/dL) and 1.45 mg/dL (range: 0.51–0.95 mg/dL) on admission. Renal histology indicated AIN; there was immune cell infiltration into the interstitium, tubulitis, and epithelial casts, although the glomeruli were largely intact. Interventions: M charantia was discontinued and prednisolone was prescribed. Outcomes: The value of serum creatinine has almost been restored to the baseline level after 3 months. Conclusion: s: This is the first case report of AIN associated with the ingestion of a pure M charantia extract. Recognition of the possible adverse effects of these agents by physicians is very important for early diagnosis and appropriate management.